La sociologie face à la crise. Una rilettura di Edgar Morin - Milani, Stella (SocietàMutamentoPolitica, 2011)
Edgar Morin is one of the few contemporary sociologists which has developed a specific theory about the crisis. He see in the crisis phenomenon a rich of opportunities to learn and know, but is essential a renewal in the theoretical and methodological instruments. Two papers, published between 1968 and 1976, marks a analytic itinerary that while show the benefits of sociological study of crisis, proposes a phenomenon’s framework within a theory of social systems. The polysemic and multiform concept of ‘crisis’ is analyzed in its constitutive dimensions; these shows the many and ambivalent implications of phenomenon, also as regards of social change theory. The Morin’s thought offers various indications, both theoretical and methodological, for overcoming the sectorial study of crisis and suggest to adopt a complex thought to catch completely the ambivalences of phenomenon.